TINJAUAN KRITIS DAN MENYULURUH TERHADAP FUNDAMENTALISME DAN RADIKALISME ISLAM MASA KINI - Siti Aisyah Abbas (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2018)
The term radicalism and religious fundamentalism is an ideology that wants to fight for ideas, revolutionary ideas that can arise from who and to anyone, also to any religion. Radicalism and fundamentalism are complex problems that do not stand alone. Almost all have very political and ideological bases. Like an ideology that continues to bind, radicalism takes the path of religion to be able to correct all anarchist actions, so Islam is not the same as radicalism. Radicalism and religious fundamentalism are actually phenomena that usually arise in any religion. Radicalism is very closely related to fundamentalism, which is marked by the return of society to the basics of religion. Fundamentalism is an